2012
DOI: 10.1387/ijdb.120020az
|View full text |Cite
|
Sign up to set email alerts
|

Noggin4 expression during chick embryonic development

Abstract: We describe here the expression pattern of Noggin4 during the early development of the chick embryo (Gallus gallus). The expression of this gene starts with the onset of gastrulation (stage HH4), in two bilateral bands along the primitive streak, with a local maximum around Hensen's node. By the end of gastrulation, Noggin4 transcripts are distributed diffusely throughout the epiblast, with the highest concentration in the head ectoderm. Interestingly, the expression of Noggin4 during the first half of gastrul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Currently three subfamilies of the Noggin family are known: Noggin1, Noggin2, and Noggin4 [1][2][3][4][5]. The data obtained in our laboratory demonstrated that secreted regulators Noggin1 and Noggin2 were involved in the binding to the proper ligands and inhi bition of three essential signal cascades, BMP, Nodal/Activin, and Wnt/betaCatenin [6,7].…”
mentioning
confidence: 79%
“…Currently three subfamilies of the Noggin family are known: Noggin1, Noggin2, and Noggin4 [1][2][3][4][5]. The data obtained in our laboratory demonstrated that secreted regulators Noggin1 and Noggin2 were involved in the binding to the proper ligands and inhi bition of three essential signal cascades, BMP, Nodal/Activin, and Wnt/betaCatenin [6,7].…”
mentioning
confidence: 79%
“…Y‐27632, a potent Rho kinase inhibitor, is known to promote the neuronal differentiation of several types of stem cells, such as human embryonic stem cells, bone marrow mesenchymal stem cells, and periodontal ligament stem cells . Noggin protein is associated with the development of various tissues, such as bones, nerve tissue, and muscles, and plays key roles in promoting somite patterning in the developing embryo by regulating bone morphogenic protein 4 (BMP4) . Rho‐associated kinase inhibitor and Noggin have been shown to play a role in recovery of spinal cord injuries after transplantation of human embryonic stem cells, but their underlying mechanism of synergistic action has not been clarified .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Noggin protein is associated with the development of various tissues, such as bones, nerve tissue, and muscles, and plays key roles in promoting somite patterning in the developing embryo by regulating bone morphogenic protein 4 (BMP4). 14 Rhoassociated kinase inhibitor and Noggin have been shown to play a role in recovery of spinal cord injuries after transplantation of human embryonic stem cells, but their underlying mechanism of synergistic action has not been clarified. 15 In this study, we aim to elucidate the mechanism underlying the synergistic effect of Y-27632 and Noggin on the proliferation and differentiation of SHEDs.…”
Section: Introductionmentioning
confidence: 99%
“…New players include Activin, Follistatin, Derrière, Coco, Mad3, BMP, Noggin4, Syndecan2 and Fgf8 [28,[34][35][36][37][38][39][40][41][42][43][44][45]. Recently, other downstream factors have been demonstrated in unilateral function during LR determination, such as calcium signalling and retinoic acid [46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%